Cell membrane capsule: a novel natural tool for antitumour drug delivery. (4th March 2019) - Zou, Hai; Zhu, Jing; Huang, Dong-Sheng
ABSTRACT: Introduction : Chemotherapy plays an important role in antitumour therapy, but causes serious adverse reactions. So, drug delivery system (DDS) with cell-targeting ability is an important method to reduce adverse reactions while ensuring the effectiveness of chemotherapy. Synthetic drug carriers and DDSs based on cells have proven safety and efficacy, but they also have many deficiencies or limitations. Cell membrane capsules (CMCs), which are based on extracellular vesicles (EVs), are a promising biomimetic DDS that retains some cell membrane channels and cytoplasmic functions, with escape macrophage phagocytosis. Areas covered : The EVs for constructing CMCs can be prepared by natural secretion, chemical-induced budding, nanofilter membrane extrusion and similar methods and are isolated and purified by a variety of methods such as centrifugation and liquid chromatography. CMCs can target the tumour cells either spontaneously or through targeting modifications using proteins or aptamers to actively target the tumour cells. CMCs can be directly wrapped with chemicals, photosensitizers, RNA, proteins and other ingredients, or they can be loaded with antitumour agent-loaded synthetic nanoparticles, which are delivered to the target cells to play a specific role. Expert opinion : This review describes the concept, function, characteristics, origins, and manufacturing methods of CMCs and their application in antitumour therapy.